Analysis of a Pilot Study Delivering Cancer Survivorship Education to Community Healthcare Professionals Utilizing the Project ECHO Model - Ashley Pariser Davenport; Kevin Johns; Dena Champion; Andrea Roberts; Susan Fugett; Erin Holley; Candice Schreiber; Carolyn J. Presley; Jalyn Todd; Andrew Honeychuck; Katherine Hunt; Yurong Lu; et al. (Taylor & Francis Group, 2024)
As the number and needs of cancer survivors grow, innovative ways to enhance survivorship expertise are needed. This pilot study evaluated a 12-week cancer survivorship curriculum delivered to two cohorts of providers at affiliated sites within the Mercy Health System, utilising the Project ECHO® model, on provider self-efficacy (SE), knowledge (KN), and professional improvement (PI). Providers received six 1-hour sessions, informed by provider needs assessment, over 12 weeks. Participants completed pre- and post-session surveys evaluating SE, KN, and PI domains. The average score for survey items overall and within each domain was compared in pre- and post-session survey results. Twenty-six participants completed the baseline survey and 22 completed the post-session survey. For cohort 1, the overall score (0.94, 95% CI [0.45,1.42] p = 0.0023), SE (1.1, [95% CI [0.5,1.7] p = 0.003), and KN domain (1.03, 95% CI [0.45,1.62] p = 0.0036) scores significantly increased. For cohort 2, the overall score (0.617, 95% CI [0.042,1.193] p = 0.0378), SE (0.728, 95% CI [0.048,1.407] p = 0.0379), and KN domains (0.665, 95% CI [0.041,1.289] p = 0.0387) increased significantly. The PI score did not change for either cohort (PI −0.09, 95% CI [−0.67, 0.49] p = 0.726 and 0.000, 95% CI [−0.790,0.790] p > 0.999). This Cancer Survivorship ECHO pilot resulted in a statistically significant increase in provider self-efficacy and knowledge. All 22 participants rated the Cancer Survivorship ECHO pilot experience as having a positive (greater than neutral) result on their training. The Cancer Survivorship ECHO model may serve as a scalable strategy for building cancer survivorship care capacity in community-based oncology practices by equipping multidisciplinary teams to meet the needs of cancer survivors within their communities. Further research is needed to assess the implementation of this model in novel settings and evaluate its impact on patient outcomes and professional improvement.